Republic of Kazakhstan : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper analyzes whether Kazakhstan has made progress in achieving a more equal income distribution, lower poverty, and a higher level of employment. Given the overarching structural challenges for Kazakhstan, the authorities are stepping up efforts to implement various measures. In order to bolster youth employment and address labor market challenges, the authorities have been revamping a college internship program and a job placement program, which will help to make educated youth competitive in the labor market and to reduce labor market mismatches. The results suggest that Kazakhstan's economic growth has been broadly inclusive; however, there is room for further improvement. Both income inequality and unemployment in Kazakhstan compare favorably to peers. Fiscal policy could be a useful tool to help reduce income inequality. Better targeting of transfers reduces their fiscal cost and tax levels required to finance them, thus achieving distributional objectives in a more efficient manner. An ambitious structural reform agenda is paramount to Kazakhstan becoming a dynamic emerging market economy and ensuring sustainable and inclusive growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet